How cutting types and shading levels influence the vegetative propagation of Pereskia aculeata? - C. C. Santos; R. da S. Bernardes; J. M. Silverio; N. M. Lima; A. Goelzer; A. dos S. Dias; S. de P. Q. Scalon; M. do C. Vieira (Brazilian Journal of Biology, 2023)
Abstract Information from Pereskia aculeata Miller (Cactaceae) responses regarding the portion of the stem cuttings branch parental plants and the shading level need to be investigated in order to establish techniques for their producing seedlings. We aimed was to evaluate the effect of cutting types and shading levels in the production of P. aculeata seedlings. We studied three cutting types, collected from different portions of the stem cuttings branch: herbaceous, semi-hardwood, and hardwood, which were arranged under two shading levels: 0% (full sun) or 50% (shade). The selected parent plants had an adequate and vigorous phytosanitary aspect. After 90 days after the cuttings, the seedlings were evaluated regarding survival, growth indicators, biomass production and partitioning, and allometric indices. Seedlings from hardwood cuttings and produced under 0% shading showed higher survival. The largest number of sprouts occurred in seedlings of semi-hardwood and hardwood cuttings. The highest leaf area values occurred in seedlings of semi-hardwood and hardwood cuttings under 0% shading. Seedlings from hardwood cuttings had higher biomass allocation in the roots under 50% shading. Seedlings of herbaceous and semi-hardwood portion allocated values ≥ 70% of the biomass in the aerial part. Seedlings of species are able to adjust to different shading levels as a plasticity mechanism. For the production of P. aculeata seedlings, the hardwood portion of the stem cuttings branch under full sun cultivation is recommended. In addition, semi-hardwood cuttings grown under 50% shading can also be used for seedlings production.